ANALISIS PEKERJAAN DAN DESAIN PEKERJAAN KARYAWAN PADA LEMBAGA RELAWAN NUSANTARA CABANG BANDUNG - Dedi Suyandi (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2023)
Abstract This study aims to analyze the work and job design of employees at the Bandung branch of the archipelago volunteer institution. This research uses qualitative methods of informant selection determined according to objectives. The implementation of the analysis is directed to review the analysis of existing positions, but in the process of extracting data remains based on the actual daily activities of the position holder through a predetermined data collection method. Job analysis is a procedure carried out by an organization to determine the responsibilities, authority and skill requirements required of the job and the type of people to be employed. Job analysis is conducted to measure and identify employee performance in order to achieve organizational goals more effectively. Job analysis is often referred to by various terms such as job analysis, activity analysis, task analysis. Job analysis can be carried out by an organization because several basic things are the reasons for carrying out the job analysis. The existence of this job analysis is useful for placing employees according to their skills and also as a realistic standard of work performance. Therefore, job analysis and job descriptions are very important to be carried out by an organization. Keywords: Job Analysis, Job Design, Job Descriptio